THE ANALYSIS OF CLASSROOM INTERACTION IN ENGLISH BETWEEN TEACHERS AND STUDENTS AT A KINDERGARTEN IN JAMBI - Nurhidayatullah, Nurhidayatullah; Hidayat, Marzul; Masita, Ella (Langue (Journal of Language and Education), 2023)
Interaction is a fundamental aspect of human life, with communication serving as a key component. In educational settings, classroom interaction plays a crucial role in facilitating effective knowledge transmission and fostering learning experiences. This study focuses on examining the patterns and quality of verbal interaction among English as a Foreign Language (EFL) students in a kindergarten classroom. This qualitative case study investigates the dynamics of classroom interaction in English between teachers and students at a kindergarten in Jambi. The research aims to gain a comprehensive understanding of the patterns of interaction, describe the types of teacher talk, and explore the characteristics of student talk. Through close observation and analysis, the study reveals compelling findings regarding the dominance of teacher talk, the varied functions of both teacher and student talk, and the emergence of significant themes within the interactions. The results demonstrate that teacher talk holds a prominent role in the classroom, influencing the learning process and managing classroom activities. However, the level of dominance displayed by the teacher varies across different learning activities. Furthermore, the study uncovers distinct types and functions of teacher talk, encompassing accepting feelings, encouraging, accepting students' ideas, asking questions, lecturing, giving directions, criticizing, and silencing. Student talk involved responding, initiating, and silencing.